Influence of electron irradiation with E = 2 MeV on electrophysical and optical characteristics of green InGaN/GaN LEDs - T. I. Mosiuk; R. M. Vernydub; P. G. Lytovchenko; Yu. B. Myroshnichenko; D. P. Stratilat; V. P. Tartachnyk; V. V. Shlapatska (Ядерна фізика та енергетика)
We studied light-emitting diodes (LEDs) with quantum dots маde on the basis of a solid solution of In0.21Ga0.79N. Measurements of current-voltage characteristics and electroluminescence characteristics were carried out in the range of 77 ÷ 300 K. On the current-voltage characteristics in the range of 77 ÷ 150 K, areas of negative differential resistance, as well as a fine structure of radiation spectra, were detected. The results of the influence of electron irradiation (Ee = 2 MeV) on electroluminescence characteristics intensity and quantum yield of the studied samples are presented; the features of the temperature dependence of the glow intensity of irradiated LEDs were revealed.